Digital transformation strategies: current research programs - N. V. Sushcheva; Yu. I. Rastova; I. G. Salimyanova (Омский научный вестник: Серия "Общество. История. Современность")
The article characterizes the key problems of strategic management of digital transformation of large companies in traditional sectors of the economy. Based on the analysis of mainly actively cited scientific publications, the main ideas of modern Russian researchers in the field of digital business transformation are summarized. Approaches to choosing a model of a corporate digital transformation strategy, methods for evaluating the effectiveness of digital transformations, and ways to form the necessary competencies are described. A number of proposals are made regarding the definition of priorities and the evaluation of effectiveness in the implementation of end-to-end technologies, as well as the digital maturity of the organizations themselves.